Note-Worthy: A Novel, Collaborative, Iterative Methodology to Analyzing Written Nurse-Physician Communication - Jeffries, Sarah; Solomon, Emilia; Burd, Daniel; Lawley, Krystal; Chiu, Tabitha; Pelc, Jordan; Lazarevic, Natasa; Joshi, Rahul (Proceedings of the International Symposium of Human Factors and Ergonomics in Healthcare, 2025)
Effective nurse-physician communication is critical for patient safety in hospitals. In this single-center post-acute care study, we investigated a written on-call communication system, known to have risks including illegibility, misinterpretation, and inappropriate triage. We developed a structured approach to analyzing written communication and optimizing on-call processes. A two-pronged methodology was employed: (1) qualitative analysis through physician observations and (2) quantitative analysis of the quality of the communication book entries. Initial findings were used to dynamically update the scoring system using an iterative study methodology. Our results yielded several insights, including demonstration of the utility of an iterative methodology; development of novel scoring criteria for nurse-physician communication; demonstration of benefits and limits of communication templates; and demonstration of limits of the well-known SBAR communication tool, which focuses on information structure, but not content, and in particular may not be helpful for triage. This study highlights the importance of interdisciplinary, iterative collaboration in creating context-specific communication tools and provides a replicable framework for future analyses of hospital communication processes.